2021
DOI: 10.1007/s10151-021-02430-x
|View full text |Cite
|
Sign up to set email alerts
|

Rubber band ligation versus haemorrhoidectomy for the treatment of grade II–III haemorrhoids: a systematic review and meta-analysis of randomised controlled trials

Abstract: Background The aim of this study was to review clinical outcome of haemorrhoidectomy and rubber band ligation in grade II–III haemorrhoids. Methods A systematic review was conducted. Medline, Embase, Cochrane Library, Clinicaltrials.gov, and the WHO International Trial Registry Platform were searched, from inception until May 2018, to identify randomised clinical trials comparing rubber band ligation with haemorrhoidectomy for grade II–III haemorrhoids. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
(56 reference statements)
0
18
0
1
Order By: Relevance
“…This result is lower than Ayman et al [25] who found this complication in ten cases (1.33 %) in their study. Dekker [2] reported a urinary retention more often after haemorrhoidectomy (2-34%) than after RBL (0-0.4%).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This result is lower than Ayman et al [25] who found this complication in ten cases (1.33 %) in their study. Dekker [2] reported a urinary retention more often after haemorrhoidectomy (2-34%) than after RBL (0-0.4%).…”
Section: Discussionmentioning
confidence: 96%
“…As reported in literature no patient with incontinence was observed [2]. In 3 studies anal incontinence was reported from 0 to 7.7% after surgical haemorrhoidectomy but this was not reported after RBL [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, patients with grade I and II and select patients with grade III haemorrhoids can be effectively treated with non-surgical therapies 3. Compared with surgical therapies, non-surgical therapies have the advantage of lower postoperative pain and complication rates, although the long-term efficacy is not as good as surgical therapies 4. Non-surgical therapies include rubber band ligation (RBL), sclerotherapy and coagulation,3 and they can all be performed via an anoscopy, proctoscopy or endoscopy.…”
Section: Introductionmentioning
confidence: 99%